Operationalizing Legitimacy - Schoon, Eric W. (American Sociological Review, 2022)
Legitimacy is widely invoked as a condition, cause, and outcome of other social phenomena, yet measuring legitimacy is a persistent challenge. In this article, I synthesize existing approaches to conceptualizing legitimacy across the social sciences to identify widely agreed upon definitional properties. I then build on these points of consensus to develop a generalizable approach to operationalization. Legitimacy implies specific relationships among three empirical elements: an object of legitimacy, an audience that confers legitimacy, and a relationship between the two. Together, these empirical elements constitute a dyad (i.e., a single unit consisting of two nodes and a tie). I identify three necessary conditions for legitimacy— expectations, assent, and conformity—that specify how elements of the dyad interact. I detail how these conditions can be used to empirically establish legitimacy (and illegitimacy), distinguishing it from dissimilar phenomena that often appear similar empirically. Followed to its logical conclusion, this operationalization has novel implications for understanding the effects of legitimacy. I discuss these implications, and how they inform debates over the relevance of legitimacy as an explanation for socially significant outcomes.